Management of Supervision of Islamic Education Based on KKG as a Professional Learning Community in Muhammadiyah Elementary School, Bandung City - Kokom Komariah; Masyitoh; Muhammad Choirin; Saiful Bahri; Suradika; Andriyani (CV. Kayaswara, 2026)
This research examines the management of Islamic Religious Education (PAI) supervision, implemented through Teacher Working Groups (Kelompok Kerja Guru/KKG), as a strategy to enhance learning quality in Muhammadiyah elementary schools in Bandung City. Employing a qualitative case study approach, the study seeks to capture the contextual dynamics of PAI supervision practices. The participants comprised PAI supervisors, Islamic education teachers, school principals, and KKG facilitators who were directly involved in supervisory and professional development activities. Data were gathered through in-depth interviews, classroom and program observations, and document reviews, and were analyzed inductively through the stages of data condensation, organization, and interpretation. The results indicate a transformation in PAI supervision practices, shifting from a predominantly administrative and bureaucratic focus toward a collaborative model grounded in professional development and data utilization. The findings also demonstrate that KKG operates as an effective Professional Learning Community (PLC), fostering teacher autonomy by applying adult learning principles. Furthermore, the alignment between the National Education Standards and the Al-Islam and Muhammadiyah values provides an ethical foundation for supervisory practices. This study introduces a Moral–Digital supervision model that combines moral leadership with the strategic use of educational data to improve the quality of PAI learning.